Combinations of avibactam and carbapenems exhibit enhanced potencies against drug-resistant Mycobacterium abscessus. (May 2017) - Kaushik, Amit; Gupta, Chhavi; Fisher, Stefanie; Story-Roller, Elizabeth; Galanis, Christos; Parrish, Nicole; Lamichhane, Gyanu
Aim: The objective of this study was to assess if avibactam, a new β-lactamase inhibitor, can restore the potency of carbapenems, a sub-class of β-lactams, against Mycobacterium abscessus clinical isolates.Materials & methods: 28 M. abscessus clinical isolates that are resistant to multiple drugs currently used to treat its infection were included. MIC of carbapenems alone and in combination with avibactam against these strains were determined.Results: Tebipenem, an oral carbapenem, and ertapenem and panipenem exhibited the greatest shift in MIC when supplemented with avibactam.Conclusion: Avibactam restores MICs of tebipenem, ertapenem and panipenem against M. abscessus to therapeutically achievable concentrations and raises the possibility of usefulness of these carbapenems to treat drug-resistant M. abscessus infections.